Nematode Economic Thresholds: Derivation, Requirements, and Theoretical Considerations - Ferris, H. (Society of Nematologists, 1978)
Determinatitm and use of economic thresholds is considered essential in nematode pest management programs. The economic efficiency of control measures is lnaximized when the difference hetween the crop valne and the cost of pest control is greatest. Since the cost of reducing the nematnde pnpnlation varies with the magnitutle of the reduction attempted, an economic (optimizing) threshold can be determined graphically or mathematically if the nature of the relationships between degree of control and cost, and nematode densities and crop value are known. Economic thresholds then vary according to the nematode control practices used, environmental influences on the nematode damage fnnction, and expected crop yields and values. A prerequisite of the approach is reliability of nematode population assessment techniques.